Legal Consequences of Disobedience of Provisional Decision of the Administrative Court - Sri Winarsi (Sriwijaya Law Review, 2024)
The existence of a legal vacuum in the State Administrative Court (PTUN) procedural law relating to the execution of the PTUN Provisional Decision raises the issue of Judicial Disobedience by state administrative institutions that do not want to carry out the PTUN Provisional Decision. Departing from this, there are two main problem formulations, namely: (1) What are the characteristics of PTUN provisional decisions? and (2) What is the formulation of legal protection against non-compliance with PTUN provisional decisions? Furthermore, this legal research uses a statutory approach, a conceptual approach, and a case approach. Based on an examination of existing legal issues, it can be concluded that provisional decisions are known in PTUN procedural law practice, where provisional decisions are submitted for matters deemed essential (urgent circumstances) by the Plaintiff to the Panel of Judges to be decided in an Interim Decision. Suppose the Party ordered by the PTUN does not implement the PTUN provisional decision. In that case, 2 (two) legal preventive mechanisms and 3 (three) legal repressive remedies can be taken in stages: 1) Sending a letter to the relevant agency, 2) Reporting to the Ombudsman, and 3) Using Criminal Law Mechanisms.